The Holy Spirit-- in biblical teaching, through the centuries, and today - Thiselton, Anthony C. (Grand Rapids, MI : William B. Eerdmans Publishing Company, 2013)
The book is divided into three parts. Part One provides a thematic analysis and exegetical commentary on all the relevant biblical and cognate literature, including Josephus, Philo and the Mishnah. Part Two investigates the thinking of key Christian theologians on the Holy Spirit, from the Apostolic Fathers to eighteenth century authors such as John Wesley and Jonathan Edwards. Part Three examines more recent writings on the Spirit, from the nineteenth century onwards, including major systematic theologians such as Schleiermacher, Barth and Moltmann, as well as biblical scholars such as James D G Dunn, Gordon Fee and Gerd Theissen. Thiselton concludes the entire study by identifying seven fundamental themes, and calling for greater dialogue between mainstream scholarship and contemporary leaders of the Pentecostal and Renewal movements.
Contents note continued: 20.Three Pentecostal or Renewal New Testament Scholars: Fee, Stronstad, and Turner -- 21.Five Major Theologians: Congar, Moltmann, Pannenberg, Lossky, and Zizioulas -- 22.Other Writers from the End of the Century: 1986-2000 -- 23.The Twenty-First Century -- 24.Summary, Conclusions, Mutual Dialogue, and Personal Reflections.
Includes bibliographical references (pages 501-521) and indexes.
Keywords: Holy Spirit -- Biblical teaching -- History; Holy Spirit -- History of doctrines